(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2013)
Starting from ancient philosophy, I define the notion of mousiké as polymorphic and polysemic artistic form, which unifies at different levels different forms of expressivity. This notion allows me to speak about translation, symbolical transformations and poetic power. In this essay I analyze the relationship between music, painting and poetry as creative symbolical universes which bring into light an ‘immaterial likeness’.